Strategi Resiliensi Umkm Seafood Dalam Menghadapi Tantangan Musim Dan Persaingan Digital Untuk Mendukung Ketahanan Pangan - Eka Renia S; Dhea Imelda; Wahyu Suryadewi; Sandy Putra P; Nadya Bryliana S (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2026)
This study aims to analyze the resilience strategies implemented by a seafood micro, small, and medium enterprise (MSME) in Kediri Regency to maintain business sustainability amid seasonal challenges and increasing digital market competition. A qualitative case study approach was employed through in-depth interviews and document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings indicate that economic necessity was the primary motivation for establishing the business. Business sustainability is supported through flexible supply chain management, adaptive product diversification, and the utilization of Facebook as the primary digital marketing platform. During periods of declining sales, the enterprise applies tactical pricing strategies and promotional activities to maintain cash flow stability. These findings demonstrate that the integration of adaptive supply chain management and digital marketing enhances the resilience and sustainability of seafood MSMEs in non-coastal areas.